Outcomes of Free Muscle Flaps versus Free Fasciocutaneous Flaps for Lower Limb Reconstruction following Trauma: A Systematic Review and Meta-Analysis - Dow, Todd; ElAbd, Rawan; McGuire, Connor; Corkum, Joseph; Youha, Sarah Al; Samargandi, Osama; Williams, Jason (Journal of Reconstructive Microsurgery, 2023)
Background Free flap reconstruction of the lower limb following trauma often suffers higher complication rates than other areas of the body. The choice of muscle or fasciocutaneous free flap is an area of active debate.Methods A systematic review of EMBASE, MEDLINE, PubMed, and Cochrane Register from inception to April 1, 2022 was performed. Articles were assessed using the methodological index for non-randomized studies instrument. The primary outcome was to assess and compare the major surgical outcomes of partial or total flap failure, reoperation, and amputation rates.Results Seventeen studies were included. All studies were retrospective in nature, of level three evidence, and published between 1986 and 2021. The most common muscle and fasciocutaneous free flaps used were latissimus dorsi flap (38.1%) and anterolateral thigh (ALT) flap (64.8%), respectively. Meta-analysis found no significance difference in rates of total flap failure, takeback operations, or limb salvage, whereas partial flap failure rate was significantly lower for fasciocutaneous flaps. The majority of studies found no significant difference in complication rates, osteomyelitis, time to fracture union, or time to functional recovery. Most, 82.4% (14/17), of the included studies were of high methodological quality.Conclusion The rate of total flap failure, reoperation, or limb salvage is not significantly different between muscle and fasciocutaneous free flaps after lower limb reconstruction following trauma. Partial flap failure rates appear to be lower with fasciocutaneous free flaps. Outcomes traditionally thought to be managed better with muscle free flaps, such as osteomyelitis and rates of fracture union, were comparable.
Keywords: free muscle flap; free fasciocutaneous flap; surgical outcomes; lower limb; trauma